Positioning Wakalah Contract on the Development of Green Sukuk Retail for Sutainable Development in Indonesia - Syamsuri; Jakiyudin, Ahmad Havid; Nurfattah, Arizqiya (LAA MAISYIR: Jurnal Ekonomi Islam, 2024)
Green retail sukuk is a new study to solve government infrastructure development problems from a funding perspective. These problems can be answered by retail green sukuk. In its application, green retail sukuk uses the construction of the wakalah contract as the basis for the contract. This study aims to examine more deeply the existence of green retail sukuk in supporting sustainable development in Indonesia and explore the position of wakalah contracts during the issuance process. A qualitative content analysis approach is used as the analytical method. This study emphasizes the context analysis of the results of a comprehensive literature study. The results showed that green retail sukuk offered two types of investment, namely Sukuk Ritel (SR) and Sukuk Tabungan (ST). Each of these types has unique and different characteristics. The application of the wakalah contract used in the two types is different, and is more dominant in the savings sukuk scheme. Even though the wakalah contract is used as the basic contract construction for the two types of retail sukuk. Promoting green retail sukuk is able to provide alternative implications for disaster mitigation in Indonesia through investment support for the development of sustainable government green projects.